The Influence of Leadership Style Motivation and Structure Employment on the Performance of Secretariat Employees North Musi rawas district - Yohanes Susanto; Wisdalia Maya Sari (Program Studi Magister Manajemen FE Unsri, 2023)
ABSTRAC Objectives:This study aims to analyze the effect of leadership style motivation and work structure, on employee performance at the regional secretariat of North Musirawas Regency, South SumatraMethodology: The population and sample of this study were employees at the regional secretariat of North Musirawas Regency as many as 50 respondents. This research is a quantitative research with Structural Equation Model (PLS-SEM) approach with Partial Least Square-Path Modeling Finding: The results of the research show that simultaneously the variables of work structure, motivation and leadership style have a positive and significant effect on employee performance, but partially the work structure has the most dominant influence on performance.Conclusion: In an organization the division of tasks and functions of each employee has been determined in the work structure, the work structure in question can be carried out properly, if the leadership role is able to control the main tasks and functions of each of his subordinates, besides that it is also supported by the level of work motivation. subordinates, each work unit in the organization is not able to work alone without coordination between work units. For this reason, efforts to improve employee performance, relations and cooperation between work units, and coordination between work units must support each other for the benefit of the organization controlled by the leadership element.